2016
DOI: 10.1007/s10853-016-0280-2
|View full text |Cite
|
Sign up to set email alerts
|

Elastic and anelastic relaxation behaviour of perovskite multiferroics I: PbZr0.53Ti0.47O3 (PZT)–PbFe0.5Nb0.5O3 (PFN)

Abstract: Perovskites in the ternary system PbTiO 3 (PT)-PbZrO 3 (PZ)-Pb(Fe 0.5 Nb 0.5 )O 3 (PFN) have attracted close interest because they can display simultaneous ferroelectric, magnetic and ferroelastic properties. Those with the most sensitive response to external fields are likely to have compositions near the morphotropic phase boundary (MPB) which lies close to the binary join Pb(Zr 0.53 Ti 0.47 )O 3 (PZT)-PFN. In the present study, the strength and dynamics of strain coupling behaviour which accompanies the dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 154 publications
0
3
0
Order By: Relevance
“…In the recent years, considerable attention of scientists and engineers was paid to ferroelectric antiferromagnets PbFe 1/2 Ta 1/2 O 3 (PFT), 𝑇 𝑁 ≈ 130-180 K, and PbFe 1/2 Nb 1/2 O 3 (PFN), 𝑇 𝑁 ≈ 140 K [37,38] and their solid solutions with PbZr 0.53 Ti 0.47 O 3 [39][40][41][42][43][44][45][46]. Some of these solid solutions exhibit roomtemperature multiferroism and large enough ME coupling, which includes a mixture of linear and biquadratic contributions.…”
Section: Giant Magnetoelectric Coupling At Room Temperature In Multif...mentioning
confidence: 99%
“…In the recent years, considerable attention of scientists and engineers was paid to ferroelectric antiferromagnets PbFe 1/2 Ta 1/2 O 3 (PFT), 𝑇 𝑁 ≈ 130-180 K, and PbFe 1/2 Nb 1/2 O 3 (PFN), 𝑇 𝑁 ≈ 140 K [37,38] and their solid solutions with PbZr 0.53 Ti 0.47 O 3 [39][40][41][42][43][44][45][46]. Some of these solid solutions exhibit roomtemperature multiferroism and large enough ME coupling, which includes a mixture of linear and biquadratic contributions.…”
Section: Giant Magnetoelectric Coupling At Room Temperature In Multif...mentioning
confidence: 99%
“…It is found that the elasticity before moving the rectangular square axis is not suitable for models based on elastic position distribution or relaxation characteristics, but is determined by the correlation between the acoustic position and the midline of relevant relaxation and / or microstructure exercises. After modification, the elasticity of fatigue factor is about 50%, which corresponds to the expected position of linear / square pressure / parameter command, but the actual operation is more complex [5]. It is an important work to explore the stability of PZT materials.…”
Section: Related Workmentioning
confidence: 99%
“…The present study was initiated as part of a wider effort to characterise the strength and mechanisms of magnetoelastic phenomena in ferroic, multiferroic and superconducting phases through the in uence of strain coupling on elastic and anelastic properties [13][14][15][16][17]. Pyrrhotites provide an interesting example of magnetoelastic behaviour in which magnetic ordering is coupled with vacancy ordering either directly or indirectly via common strains.…”
Section: Introductionmentioning
confidence: 99%